Impacto da mobilização passiva como estratégia reabilitadora na função endotelial de pacientes críticos com diagnóstico de sepse - Silva, Tamara Rodrigues da (Universidade Federal de São Carlos, 2018)
Endothelial dysfunction (ED) plays a key role in the pathogenesis of sepsis and the exercise stimulus influence the vascular endothelium. As a rehabilitative strategy, early mobilization is beneficial when performed in critically ill patients. However, there is still a lack of evidence regarding the acute effects of passive mobilization (PM) on endothelial function (EF). Objective: to investigate EF response after a protocol of PM in patients with sepsis. Methods: 25 patients diagnosed with sepsis and septic shock, admitted to an intensive care unit participated in the study. EF was assessed by flow-mediated dilatation (FMD) of the brachial artery before and immediately after the PM protocol, considering relative, absolute and normalized FMD variables. The peak flow velocity at baseline and during reactive hyperemia (RH) and the shear rate were also considered. The PM protocol consisted of 3 sets of 10 repetitions of mobilization of the following joints: ankles, knees, hips, wrists, elbows and shoulders. The paired t-test was used for the comparisons with p <0.05. Results: The relative FMD increased after performing the PM (5.07±8.97% to 17.07±8.08%, respectively) (p <0.001). Similarly, absolute (0.17±0.31mm to 0.57±0.22mm) and normalized FMD (0.0013±0.0031mm/s to 0.0024±0.0015mm/s) also showed higher values after PM. The peak flow velocity after RH (71.85±29.34cm/s to 95.32±32.28cm/s) and the shear rate (210.82±110.43s to 288.48±140.88s) were also higher after PM (p <0.001). Conclusion: The stimulation of passive mobilization as a rehabilitation strategy applied to critical patients with a diagnosis of sepsis was able to increase acute endothelial function.
Early passive mobilization increases vascular endothelium function in critically ill patients with sepsis in ICU.
Keywords: Sepse; Função endotelial; Dilatação mediada pelo fluxo; Mobilização passiva; Endothelial function; Sepsis; Flow-mediated dilation; Passive mobilization; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL